Scott-representability of some spaces of Tall and Miskin - Harold Bennet; David Lutzer (Applied General Topology, 2008)
In this paper we show that a variation of a technique of Miskin and Tall yields a cocompact completely regular Moore space that is Scott-domain-representable and has a closed Gδ-subspace that is not Scott-domain-representable. This clarifies the general topology of Scott-domain-representable spaces and raises additional questions about Scott-domain representability in Moore spaces.